Religiosity and its predispositions among post-secondary students in Malaysia: a systematic review - Yong, Claudia; Nor Zainudin, Zaida; Mohd Anuar, Mohd Ashraff; Wan Othman, Wan Norhayati (Human Resource Management Academic Research Society, 2023)
Religion is a personal set or institutionalized system of religious attitudes, beliefs, or both, which may exert certain degree of influence to one’s life. As reported by Gallup International in 2012, Malaysia is a highly religious society. Therefore, it could be assumed that religion permeates deep in the lives of all levels of Malaysian society including post-secondary students. Investigation on religiosity among post-secondary students is necessary as emerging research has outlined the importance of religion in shaping post-secondary students’ ideals, goals, and habits. Not only that, investigation on religion in classically pluralistic Malaysia could yield novel insights as religiosity in this specific context has idiosyncratic dimensions and its influences are multifold. Accordingly, the objective of this review includes to investigate how religiosity predispose students to certain outcomes and how religiosity of students in Malaysia were measured in previous studies. In addition, this review also identified some the gaps and limitation in the literature concerning investigation of religiosity of students in Malaysia. Summarily, this review found evidence to corroborate effects of religiosity to students’ cognition, emotions, as well as behavior. Furthermore, this review also noted that most of the studies utilized cross-sectional survey method which prompted suggestions to improve research methodology in future efforts. Other recommendations include to consider facets of religiosity and the underlying factors that could influence effects of religiosity. In short, this review highlighted insights that could benefit not only post-secondary students, but also all other actors in their social ecologies which encompass tertiary education authorities, mental health helpers, and other policymaking bodies.